Determinants of National Guard Mental Health Service Utilization in VA versus Non‐VA Settings. (3rd February 2016) - Gorman, Lisa A.; Sripada, Rebecca K.; Ganoczy, Dara; Walters, Heather M.; Bohnert, Kipling M.; Dalack, Gregory W.; Valenstein, Marcia
Abstract : Objective: To determine associations between need, enabling, and predisposing factors with mental health service use among National Guard soldiers in the first year following a combat deployment to Iraq or Afghanistan. Data Sources/Study Setting: Primary data were collected between 2011 and 2013 from 1, 426 Guard soldiers representing 36 units. Study Design: Associations between Guard soldier factors and any mental health service use were assessed using multivariable logistic regression models in a cross‐sectional study. Further analysis among service users ( N  = 405) assessed VA treatment versus treatment in other settings. Principal Findings: Fifty‐six percent of Guard soldiers meeting cutoffs on symptom scales received mental health services with 81 percent of those reporting care from the VA. Mental health service use was associated with need (mental health screens and physical health) and residing in micropolitan communities. Among service users, predisposing factors (middle age range and female gender) and enabling factors (employment, income above $50, 000, and private insurance) were associated with greater non‐VA services use. Conclusion: Overall service use was strongly associated with need, whereas sector of use (non‐VA vs. VA) was insignificantly associated with need but strongly associated with enabling factors. These findings have implications for the recent extension of veteran health coverage to non‐VA providers.